Autophagy Induced by Proteasomal DUB Inhibitor NiPT Restricts NiPT-Mediated Cancer Cell Death - Chen, Jinghong; Chen, Xin; Xu, Dacai; Yang, Li; Yang, Zhenjun; Yang, Qianqian; Yan, Ding; Zhang, Peiquan; Feng, Du; Liu, Jinbao (Frontiers in Oncology, 2020)
Ubiquitin–proteasome system (UPS) and autophagy–lysosome pathway (ALP) are two major systems for protein quality control (PQC) in eukaryotic cells. Interconnectivity between these two pathways has been suggested, but the molecular detail of how they impact each other remains elusive. Proteasomal deubiquitinase (DUB) is an important constituent in the UPS and has proved to be a novel anticancer target. We have previously found that a novel DUB inhibitor, nickel complex NiPT, induces apoptosis in both cultured tumor cell lines and cancer cells from acute myeloid leukemia human patients. In this study, we found that NiPT triggered autophagy both in vitro and in vivo. Mechanistically, NiPT targets two DUBs, USP14, and UCHL5, and increased the total cellular level of polyubiquitination. Deletion of the Ubiquitin Associated (UBA) domain of P62 that is required for polyubiquitin binding prevented NiPT-induced autophagy. NiPT-induced autophagy is through either concomitant activation of AMP-activated protein kinase (AMPK) and inhibition of mechanistic target of rapamycin (mTOR) signaling, or eliciting endoplasmic reticulum (ER)-stress by activating activating transcription factor 4 (ATF4) and C/EBP-homologous protein (CHOP). Moreover, NiPT could induce more lung cancer cells undergoing apoptosis if it synergistically uses autophagy inhibitors, suggesting that NiPT-induced autophagy protects cancer cell from death. Collectively, our findings demonstrate that autophagy inhibition enhances the anticancer effects of proteasomal DUB inhibitor and might be an effective treatment strategy for lung cancer.